Using learner verification and transcreation to develop multicultural patient education materials for acute respiratory tract infections to decrease inappropriate antibiotic prescribing - Rebecca K. Rudel; Emma Powers; Kirsten Austad; Shana A.B. Burrowes; Zaire Couloute; Anais E.C. Smith; Christine Prifti; J. Morgan Freiman; Robin Wigmore; Allan Walkey; Jacqueline M. Hicks; Tamar F. Barlam; et al. (PEC Innovation)
Objective: Patient demand often drives inappropriate antibiotic prescribing for acute respiratory tract infections (ARTI). This study aimed to develop novel culturally- and linguistically-tailored patient education material regarding appropriate ARTI care. Methods: This qualitative study used a four-phase approach to develop single-page English, Spanish, and Haitian Creole patient education materials for appropriate ARTI treatment designed for clinical use: 1) material development informed by pre-existing materials, 2) learner verification, 3) revision, and 4) transcreation. Patient and provider focus groups and interviews were conducted at three Massachusetts health systems. Transcripts were coded and analyzed using a framework informed by the Patient Education Materials Assessment Tool. Results: Twenty-six providers and 48 patients (27 English, 10 Spanish, 11 Haitian Creole speaking) participated. Participants suggested improving readability by replacing text blocks with bulleted lists and usability by providing self-care solutions. The transcreation process resulted in literal translations that were unclear to Spanish and Haitian Creole speakers, who provided culturally-appropriate suggestions. Innovation: Patient education materials are co-created with diverse patient and provider populations to create culturally-tailored materials, available in multiple languages, for ARTI treatment. Conclusion: Learner verification, revision, and transcreation can result in understandable and actionable materials for patients in multiple languages. Materials may help decrease demand for and rates of inappropriate antibiotic prescribing for ARTI.